2016
DOI: 10.1017/s0014479716000636
|View full text |Cite|
|
Sign up to set email alerts
|

Operationalizing an Innovation Platform Approach for Community-Based Participatory Research on Conservation Agriculture in Burkina Faso

Abstract: SUMMARYNumerous innovation platforms have been implemented to encourage the adoption of agricultural innovations and stakeholder interactions within a value chain. Yet little research has been undertaken on the design and implementation of innovation platforms focussing on issues other than market access and aiming to encourage agro-ecological intensification. This is the case for the development of Conservation Agriculture (CA) in West Africa, which due to its complex nature calls for technical, organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…In order to avoid repeating the shortcomings of earlier learning methods such as farmer field schools, policymakers must carefully consider aspects of sustainability in the design and implementation of learning programs. Since IPs in the study site depend on donor support (Ragasa et al 2016;Dabire et al 2017;Schut et al 2018), the following lessons may be used by policymakers while designing and implementing learning programs: To begin with, IPs such as Mt.Elgon women in coffee developed and are enforcing bi-laws to control fake inputs and coffee products in collaboration with the local government. Joint development and implementation of bilaws is an opportunity that can be drawn and used to help farmers learn more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid repeating the shortcomings of earlier learning methods such as farmer field schools, policymakers must carefully consider aspects of sustainability in the design and implementation of learning programs. Since IPs in the study site depend on donor support (Ragasa et al 2016;Dabire et al 2017;Schut et al 2018), the following lessons may be used by policymakers while designing and implementing learning programs: To begin with, IPs such as Mt.Elgon women in coffee developed and are enforcing bi-laws to control fake inputs and coffee products in collaboration with the local government. Joint development and implementation of bilaws is an opportunity that can be drawn and used to help farmers learn more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some support mechanisms like innovation platforms (i.e., groups of individuals with different backgrounds but common innovation goals) can help resolve problems that producers and other actors encounter during the agroecological transition. As observed in different contexts in Africa (Dabire et al 2017;Angbo-Kouakou et al 2018), the success of these platforms is based upon several principles: construction and exchange of knowledge between actors; facilitation of collective action; strengthening or development of collaborative practices between multiple organizations with sometimes divergent interests; and facilitation of planning of action and the monitoring, evaluation, and capitalization of experimental activities.…”
Section: Levers For Action At the Local Level To Support Producersmentioning
confidence: 99%
“…Such studies have shown that the design of innovative agricultural systems has to involve technical, social, and organizational changes and to be analyzed and implemented with stakeholders at multiple levels (Delmotte et al, 2016;Moraine et al, 2016). Participatory mechanisms such as multiactor innovation platforms associated with exploration tools, such as modeling tools or on-farm experiments, are key in such processes to facilitate mediation and the development of a common language among partners (Dabire et al, 2016). Such multi-actor innovation platforms can be defined as networks intended to strengthen interactions between actors in order to facilitate change that enables innovation (Kilelu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%